The impact of red culture integration in environmental education on college students’ ecological ethical identity: An empirical analysis from environmental social psychology - Rong Li (Environment and Social Psychology, 2025)
Based on environmental social psychology theory, this study systematically investigated the impact mechanisms of red culture integration into environmental education on college students’ ecological ethics identity through a mixed-methods approach combining quasi-experimental design with large-scale surveys. Through surveys of 1,200 college students from four regions nationwide and quasi-experimental research involving 160 students, the findings revealed that red culture integration into environmental education had a significant positive impact on college students’ ecological ethics identity (β=0.616, p<0.001). The experimental group students’ ecological ethics identity scores significantly improved from 4.82 in the pretest to 5.45 in the posttest, with an effect size of 0.95, indicating a large effect level that remained significant in delayed posttests. Mediation effect analysis revealed that cognitive processing mechanisms (52.9%), emotional experience mechanisms (66.9%), and social learning mechanisms (48.4%) played important mediating roles in the educational impact process, with emotional experience mechanisms demonstrating the strongest mediation effect. Particularly, the mediating role of national pride reached 70.9%, reflecting the unique advantages of red culture in emotional appeal. Moderation effect analysis found that individual characteristics (political identity level, environmental concern degree, cultural background differences), educational contextual factors (teaching methods, curriculum design elements, learning environment atmosphere), and sociocultural factors (regional cultural differences, family educational background, media exposure level) significantly moderated the educational effects, presenting obvious individual differentiation and contextual dependency characteristics. The research results indicate that red culture integration into environmental education effectively promoted the formation and development of college students’ ecological ethics identity through multiple pathways including stimulating national identity, promoting value reconstruction, and providing role model demonstrations. This study not only enriches the theoretical framework of environmental social psychology but also provides important empirical support and practical guidance for ecological civilization education model innovation and red culture inheritance and development in the new era.